2007
DOI: 10.1002/macp.200600622
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Temperature Sensors with Tunable Properties

Abstract: Thermochromic polymer/dye blends based on small amounts (0.6–2.3 wt.‐%) of chromogenic sensor dyes and glassy amorphous polymers were prepared. Subjecting melt‐processed, quenched blends to temperatures above Tg leads to permanent and pronounced changes of their absorption and fluorescence spectra as a result of phase separation and assembly of dye aggregates. The influence of dye structure and polymer Tg on the aggregation kinetics of these blends was investigated. It is shown that increasing the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 56 publications
3
76
0
Order By: Relevance
“…Indeed, the slope of the curve with 5 wt% of DCM is first higher and then lower than the slope of the curve with 0.5 wt% of DCM, which evidences the presence of both types of aggregates. This observation is fully consistent with a systematic study of dye aggregation reported in [66]. In fact, to optimize the optical quality of the dye-doped PMMA layer, it is annealed at 120…”
Section: Appendix B: Fluorescence Anisotropysupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, the slope of the curve with 5 wt% of DCM is first higher and then lower than the slope of the curve with 0.5 wt% of DCM, which evidences the presence of both types of aggregates. This observation is fully consistent with a systematic study of dye aggregation reported in [66]. In fact, to optimize the optical quality of the dye-doped PMMA layer, it is annealed at 120…”
Section: Appendix B: Fluorescence Anisotropysupporting
confidence: 89%
“…above the T g of PMMA. As reported in [66], this process "leads to irreversible phase separation and the formation of dye aggregates". In consequence, the fluorescence lifetimes were measured with slightly doped layers (0.5 wt%), and lead to 1.8 ns for DCM, 2.6 ns for RH640 and 1.5 ns for PM605, in consistence with measurements reported elsewhere [70].…”
Section: Appendix B: Fluorescence Anisotropymentioning
confidence: 85%
“…The approach exploits the excimer-forming properties of chromophores such as cyano-substituted oligo(phenylene vinylene)s [7][8][9][10][11][12] (cyano-OPVs, Figure 1) and further relies on the stimulus-driven self-assembly or dispersion of nano-scale aggregates of these sensor dyes in a range of host polymers. We have shown that this general concept of stimulus-triggered dye (dis)assembly in polymer matrices allows for the design of a broad range of sensor materials, which are useful for the detection of temperature history, [13][14][15][16][17] exposure to chemicals, [18,19] and mechanical deformation, [20][21][22][23][24] as well as more complex combinations of stimuli, such as seen in shape-memory materials. [25] Others have adapted the concept and extended it to a range of dyes including cyano containing poly(phenylene ethynylenes), [26] perylenes, [27] CdS nanoparticles, [28] and bis(benzoxazolyl)stilbenes.…”
Section: Introductionmentioning
confidence: 99%
“…This approach yields timetemperature indicating materials that exhibit a pronounced fluorescence color change, whose kinetics follow a predictable, Arrhenius-type behavior. [14][15][16][17] For humidity sensors, a hygroscopic host polymer is chosen, which has a T g that is above the desired working temperature. [18] Moisture serves to plasticize the matrix thus lowering T g and providing the mobility to facilitate the aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…While the study did also not involve well-defined supramolecular assemblies, the results paved the way for subsequent work on mechanochromic polymers comprising assemblies of aggregachromic, excimer-forming cyano-substituted oligo(p-phenylene vinylene)s (cyano-OPVs, Figures 2-4). [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Scanning confocal microscopy images of blend films of ultra-high-molecular-weight polyethylene and 10 -4 % w/w EHO-OPPE (Figure 1). a) As prepared film.…”
Section: π-π Interactionsmentioning
confidence: 99%